How to coordinate the use and conservation of natural resources in protected areas: From the perspective of tourists’ natural experiences and environmentally responsible behaviours - Zhang, Yuling; Cao, Ruibing; Xiao, Xiao; Wei, Zongcai; Yang, Jianbo; Gao, Yu’nan; Lu, Song; Zheng, Chunhui (Frontiers in Environmental Science, 2022)
One of the important purposes of opening protected areas to the public is providing tourists with natural experience products and education so as to stimulate their environmentally responsible behaviours (ERBs) and achieve sustainability. However, there are often contradictions between the recreational use of natural resources and eco-environmental protection, and scholars have not directly determined whether natural experiences always trigger tourist ERBs. To fill this gap, we study the formation of ERBs (including environmentally friendly behaviours, environmental concern-based behaviours and sustainable behaviours) by integrating the mechanisms of tourists' experiences (including sensory experience, mental involvement and norm arousal) and their effects on ERBs. The results of a sample of 682 tourists at a National Nature Reserve in China affirm that there are spillover effects among tourists' experiences and that tourists' experiences influence ERBs. Sensory experience and norm arousal positively affect people’s environmentally friendly behaviours, their behaviours that are based on their concern for the environment and their sustainable behaviours. While mental involvement has a positive impact on environmentally friendly behaviours, a negative impact on sustainable behaviours, and no effect on people’s environmental concern-based behaviours. In addition, mental involvement and norm arousal play an important role in mediating the impacts of sensory experience on ERBs. This study explores the relationship between use and conservation of natural resources via tourists’ experiences and ERBs, and it reveals that tourists' experience stays in mental involvement, which may not conducive to eco-environmental conservation in the protected areas. It opens the field for future research paths in the exploration of the paradox that emerges out of the natural experience and tourists' ERBs and provides insights into and points to ecological implications for reserve managers and tourism operators.